Yield and Cost of Performing Screening Tests for Constipation in Children. (2013) - Chogle, Ashish; Saps, Miguel
Abstract : BACKGROUND: Chronic constipation is one of the most common reasons for pediatric outpatient visits. Clinical guidelines recommend that the work-up for chronic refractory constipation include thyroid function tests, celiac serology, and measurement of calcium and lead levels. Data to justify routine screening of constipated children using these laboratory tests are lacking. OBJECTIVES: To study the prevalence of celiac disease, hypothyroidism, hypercalcemia and lead poisoning in children with chronic constipation; and to estimate the health care costs of applying the guideline recommendations. METHOD: Charts of constipated children from 2007 to 2011 were reviewed for the present retrospective cohort study. Results and costs of thyroid function tests, celiac panel, total immunoglobulin (Ig) A, and determination of lead and calcium levels were analyzed. RESULTS: A total of 7472 children (mean age 7.9 years; 3908 female) were evaluated: 1731 patients were screened for celiac antibodies; 55 had elevated tissue transglutaminase IgA levels and 29 had biopsy-positive celiac disease. Only three celiac patients had constipation as the sole presenting symptom; 1703 patients were screened for total IgA levels; 55 had IgA deficiency and two had biopsy-positive celiac disease; 2332 had free T4 and/or thyroid-stimulating hormone levels; and 14 had hypothyroidism. Only two patients had constipation as the sole presenting symptom; 4651 patients had calcium levels measured, 10 of whom had high levels but normal repeat values. Three patients had normal lead levels. The mean cost per patient was USD1, 014. Total screening cost for all patients was USD4.7 million. CONCLUSION: Constipation alone did not increase the likelihood of celiac disease or hypothyroidism above the population prevalence. No benefit of screening for hypercalcemia was found. High health care costs were associated with the use of screening tests for organic constipation.